Kaweng Heka : Kajian PAK Dan Implikasinya - Hekmin Hukunala; Flavius Andries; Fransisca Jallie Pattiruhu (Concept: Journal of Social Humanities and Education, 2023)
Kawin Lari or Kaweng Heka is a marriage carried out by a boy and a girl with the aim of living together. The reason they eloped because their love relationship was not approved by the male's parents. In this study, a qualitative approach was used with an analytic descriptive method, meaning that the data obtained was in the form of words, descriptions, behavior, not in the form of numbers or statistics, but in a qualitative form, which has a richer meaning than just a number or frequency. The research location is located in Wamkana Village, Namrole District, South Buru Regency. So, kaweng heka is really an act that is not in line with the principles of God's Word contained in the Bible and apart from that, this is also an act that is not in accordance with the norms prevailing in society. It will be more beautiful and happier if the marriage is carried out in a good and proper way, so that it does not cause disgrace and also problems in the community and also in the families of both parties or the couple who elopes (Heka). Based on the results of the research and discussion, it can be concluded that basically eloping (kaweng Heka) that occurred in Wamkana village was for two people who both liked and wanted to get married but were hindered by several factors such as not getting the blessing of their parents. , because the dowry is too expensive, social status and so on. Although in the past there were cases of eloping (kaweng heka) because they violated religious values, this rarely happened, it is different from now, then the loss of religious values ​​and customary norms has become one of the factors in the large number of elopeds occurring because of violating values. religion. The thing that causes heka marriage (elope) is because it has violated religious values, besides that it is also because of the child's rather free association and lack of parental control.